New cationic palladium (II) and rhodium (I) complexes of [Ph2PCH2C(Ph)=N(2,6-Me2C6H3)] - Pascu, SI; Coleman, KS; Cowley, AR; Green, MLH; Rees, NH (Journal of Organometallic Chemistry, 2005)
Treatment of the bulky iminophosphine ligand [Ph2PCH2C(Ph)=N(2,6-Me2C6H3)] (L) with [M(CH3CN)(2)(ligand)](+n), where for M = Pd(II): ligand = eta(3)-allyl, n = 1, and for M = Rh(I), ligand: 2(C2H4), 2(CO) or cod, n = 0, yields the mono-cationic iminophosphine complexes [Pd(eta(3)-C3H5)(L)][BF4] (1), [Rh(cod)(L)][BF4](2), [Rh(CO)(CH3CN)(L)][BF4](3), and ciY-[Rh(L)(2)][BF4](4). All the new complexes have been characterised by NMR spectroscopy and X-ray diffraction. Complex I shows moderate activity in the copolymerisation of CO and ethene but is inactive towards Heck coupling of 4-bromoacetophenone and n-butyl acrylate. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: rhodium(I); Pd(II)-allyl; iminophosphines; CO ethylenecopolymerisation; Heck reactionsX-RAY CRYSTAL; CATALYZED ALLYLIC SUBSTITUTION; MOLECULAR-STRUCTURES; CARBON-MONOXIDE; STRUCTURAL-CHARACTERIZATION; IMINOPHOSPHINE LIGANDS; ASYMMETRIC CATALYSIS; N LIGANDS